The statistical analysis for the theoretical bio-methane market based on the opinion of car-owners of Hajdú-Bihar county in Hungary - Barta-Juhász, Lilla I. (Applied Studies in Agribusiness and Commerce, 2013)
The more expensive fuels and the health-threatening air pollution make even necessary the spread of such a fuel, which serves as a solution to these problems. In our country at present there are three public CNG filling stations, two of them are located in Gyôr and Szeged and the third one was opened at the end of October in Budapest. The lack of infrastructure obstructs the spread of the methane gas powered cars in Hungary. During my research getting information by means of a test questionnaire I measured the fuel selection of the drivers and their opinion about alternative fuels. Then on the basis of the results I determined the potential target audience of the bio-CNG. As it is also typical in our country, the most of the respondents use gasoline-powered vehicle and drive less than 12 000 km/year on an average. 55% of the respondents would have their car converted in order to refuel cheaper and to protect the environment, consequently there would be demand for CNG. The potential target audience is the urban population below the age of 41 with higher education degree and average salary. One of my future objectives is to design a CNG filling station network in Hajdú-Bihar county considering the demand of car owners.